2018
DOI: 10.1186/s12864-018-4831-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing identification of miRNAs in pigeon ovaries illuminated with monochromatic light

Abstract: BackgroundThe use of light of different wavelengths has grown popular in the poultry industry. An optimum wavelength is believed to improve pigeon egg production, but little is known about the role of microRNAs (miRNAs) in the effects of monochromatic light on ovarian pigeon function. Herein, we harvested ovaries from pigeons reared under monochromatic light of different wavelength and performed deep sequencing on various tissues using an Illumina Solexa high-throughput instrument.ResultsWe obtained 66,148,548… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This tendency showed the same trend as that seen in our results. Similarly, Wang et al ( 2018) also reported miR-122 to be a candidate miRNA involved in the effects of monochromatic light on pigeon reproduction [40]. Therefore, the upregulation of chi-miR-122 may be a useful strategy to increase ovulation rates in goats.…”
Section: Discussionmentioning
confidence: 94%
“…This tendency showed the same trend as that seen in our results. Similarly, Wang et al ( 2018) also reported miR-122 to be a candidate miRNA involved in the effects of monochromatic light on pigeon reproduction [40]. Therefore, the upregulation of chi-miR-122 may be a useful strategy to increase ovulation rates in goats.…”
Section: Discussionmentioning
confidence: 94%
“…In the present study, three embryonic developmental stages of C. quadricarinatus, including the eye pigment forming stage, prepare-hatching stage, and larva, were selected by small RNA-Seq technology to identify miRNAs and acquire their expression profiles. In the previous reports, transcriptome libraries have been successfully used to search for novel miRNAs and predict target genes in some organisms (Niu et al, 2014;Wang et al, 2018). Although an annotated genome was lacking in C. quadricarinatus to identify miRNAs, the transcriptome of embryogenesis contributed to miRNAs recognition in this study.…”
Section: Discussionmentioning
confidence: 95%
“…By studying the pectoral muscle miRNAs of pigeons at different age stages, 89 miRNAs and pathways of MAPK and TGF-β were found to be related [17]. MiR-205b was thought to play a key role in monochromatic light regulation of pigeon egg production [20].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the miRNA expression profile of the oral mucosa infected by T. gallinae of pigeons was designed to analyze the potential genes and related miRNAs. Previous studies in pigeon miRNAs have been focused on crop tissues [4], pectoral muscle and ovaries [20]. In the study of crop tissues, miR-20b-5p, miR-146b-5p, miR-21-5p and miR-26b-5p were found to regulate lactation [4].…”
Section: Discussionmentioning
confidence: 99%